2005
DOI: 10.1002/cbic.200500261
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Ethane to Ethanol by Engineered Cytochrome P450 BM3

Abstract: Picking on someone smaller. Cytochromes P450 catalyze the hydroxylation of thousands of substrates, including alkanes. No naturally occurring P450, however, is known to oxidize the smallest alkanes, ethane and methane. Here we report the direct and selective oxidation of ethane to ethanol using dioxygen, catalyzed by a cytochrome P450 BM‐3 variant engineered for high activity towards small alkanes (see scheme). Achieving P450‐catalyzed oxidation of ethane is a key step in the pathway to P450‐catalyzed methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
117
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 28 publications
0
117
0
5
Order By: Relevance
“…Exciting recent results with the bacterial enzyme P450 BM3 have illustrated the potential of directed evolution for engineering P450s that use artificial oxygen donors (Glieder et al, 2002;Meinhold et al, 2005). Recently, P450 BM3 has been engineered by directed evolution to produce the authentic human metabolites of propranolol (Otey et al, 2006).…”
mentioning
confidence: 99%
“…Exciting recent results with the bacterial enzyme P450 BM3 have illustrated the potential of directed evolution for engineering P450s that use artificial oxygen donors (Glieder et al, 2002;Meinhold et al, 2005). Recently, P450 BM3 has been engineered by directed evolution to produce the authentic human metabolites of propranolol (Otey et al, 2006).…”
mentioning
confidence: 99%
“…Key to the activity of sMMO is the proposed diiron µ-oxo active site ( Figure 1) [81]. More recently Meinhold et al have shown engineered variants of P450 BM3 to be active for the fast oxidation of ethane to ethanol, with turnover frequencies mol ethanol¨m ol protein´1¨h´1 of 500 reported, at an NADPH oxidation rate of 31,200 h´1 [82]. The active site for P450 is shown in Figure 2.…”
Section: Enzymatic Approachesmentioning
confidence: 99%
“…Crucially, sMMO was able to avoid production of deeper oxidation products acetic acid and CO2. Key to the activity of sMMO is the proposed diiron μ-oxo active site (Figure 1 [82]. The active site for P450 is shown in Figure 2.…”
Section: Enzymatic Approachesmentioning
confidence: 99%
“…Characteristics such as thermostability (10), solvent tolerance (25), enantioselectivity (7), substrate specificity (8), and catalytic efficiency (9) have all been altered to better adapt enzymes for specific purposes. Several examples applying molecular evolution to CYP enzymes have also been described in the literature, including the modification of the substrate specificity of the CYP BM3 from Bacillus megaterium (18,33). The wild-type CYP BM3 hydroxylates long-chain fatty acids predominantly in the -2 position.…”
mentioning
confidence: 99%
“…Site-directed mutagenesis provided mutants able to hydroxylate shorter-chain fatty acids and cyclic hydrocarbons. Multiple rounds of molecular evolution were necessary to adapt the enzyme to catalyze the direct hydroxylation of first octane, then propane, and finally ethane as a substrate (18).…”
mentioning
confidence: 99%